The Correlation of Age, Gender, Heredity, Smoking Habit, Obesity, and Salt Consumption with Hypertension Grade in Cirebon, Indonesia - Alif Hamzah; Uswatun Khasanah; Dini Norviatin (GHMJ (Global Health Management Journal), 2019)
Background: Hypertension is one of the most global killer diseases that causes death. The World Health Organization estimated around 1.5 billion people in the world will be diagnosed with hypertension every year. The increasing incidences of hypertension in the world may be affected by several predictors including age, sex-linked, heredity, smoking habit, obesity, and salt consumption. This study has objective to examine those predictors to hypertension grade. Methods: This research was used observational analytic method with cross-sectional study. This study involved 136 respondents who came to Kalijaga Permai Public Health Center, Cirebon City. The variables were measured by microtoise, sphygmomanometer, stethoscope, scales, and questionnaires. Spearman correlation test and logistic regression test was analyzed for this study. Results: 59.9% of respondents were in hypertension grade 1 and 54% of respondents were in high risk age. The bivariate results revealed that age, sex-linked, heredity, and salt consumption were statistically correlated with hypertension grade (p=0.001). However, smoking habit and obesity were not statistically correlated. Multivariate analysis found that those who add extra salt were 3.3 times more likely to have hypertension grade 2 and those in high risk age were 3.1 more likely to have hypertension grade 2 as well. Compared with female and those who have negative heredity, male and positive heredity were 2.7 times more likely to have hypertension grade 2. Conclusion: Salt consumption, age, sex-linked, heredity was significantly correlated with hypertension grade. Salt consumption was a risk factors which has the highest impact. Public health center should educate people about the recommendation of daily salt intake to prevent the excessive intake that may affect hypertension. Keywords: hypertension, smoking habit, obesity, salt consumption, age, gender, heredity Received: 26 April 2019 Reviewed: 27 May 2019 Revised: 17 June 2019 Accepted: 12 July 2019 DOI: 10.35898/ghmj-33586